2009
DOI: 10.1103/physrevb.80.115213
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced phase transitions in amorphous and metastable crystalline germanium by Raman scattering, x-ray spectroscopy, andab initiocalculations

Abstract: A detailed study of the pressure-induced phase transitions in amorphous Ge ͑a-Ge͒ up to 17 GPa is reported combining Raman scattering, x-ray absorption spectroscopy ͑XAS͒ measurements, and density-functional theory calculations. a-Ge samples were films obtained by evaporation and characterized by different density of voids. Specific and reproducible phase transitions ͑interpreted as disorder-disorder, disorder-order, and order-disorder͒ are observed on pressurization and depressurization, depending on the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 39 publications
(41 reference statements)
7
44
0
Order By: Relevance
“…74 These features were previously assigned to the BC8 and R8 structures, 74 and this metastable back-transformation was also observed for germanium (ST 12 structure). 75 Thus, we suggest that the reflective regions observed in the photomicrographs originate from metallic silicon and, by analogy, to the strikingly similar photos from Chen et al 14 We suggest that metallic silicon can explain the abrupt changes in infrared reflectivity and electrical resistance associated with previous reports of metallization. The loss of Raman signal observed here during decomposition is similar to previous reports where silane was claimed to metallize.…”
supporting
confidence: 84%
“…74 These features were previously assigned to the BC8 and R8 structures, 74 and this metastable back-transformation was also observed for germanium (ST 12 structure). 75 Thus, we suggest that the reflective regions observed in the photomicrographs originate from metallic silicon and, by analogy, to the strikingly similar photos from Chen et al 14 We suggest that metallic silicon can explain the abrupt changes in infrared reflectivity and electrical resistance associated with previous reports of metallization. The loss of Raman signal observed here during decomposition is similar to previous reports where silane was claimed to metallize.…”
supporting
confidence: 84%
“…19 The difference in the behaviour of Ge-Ge distance as compared to the previous reports is drastic. We observe no sharp change in the distance throughout the whole pressure range.…”
mentioning
confidence: 59%
“…Some authors observe the formation of the unstable bc8-Ge phase followed by the kinetically stable hd-Ge structure (Imai et al, 1996;Minomura, 1981), while others report (like for a-Si) a metallic high-density form of a-Ge under pressure rather than (β-Sn)-Ge (Barkalov et al, 2010;Cicco et al, 2008;Coppari et al, 2009;Principi et al, 2005). On unloading, the reappearance of a low-density a-Ge phase was observed in some cases (Cicco et al, 2008;Principi et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…On unloading, the reappearance of a low-density a-Ge phase was observed in some cases (Cicco et al, 2008;Principi et al, 2005). Indeed, Coppari et al (2009) have suggested that voids observed in the type of a-Ge used in their experiments may account for crystalline/amorphous differences observed in their experiments. This may suggest that the differences between the transformation behavior of a-Ge and dc-Ge reported in the literature may relate, just as for a-Si, to morphology and impurity content within the form of a-Ge used for the various DAC experiments.…”
Section: Introductionmentioning
confidence: 92%